Positive correlation between ELF and RFelectromagnetic fieldon cancer risk - Mahdavi, Majid; Yekta, Reza; Hesami Tackallou, Saeed (Archives of Advances in Biosciences, 2015)
Extremely low frequency (ELF) and Radio frequency (RF) electromagnetic field may affect biological systems by raising generation free radicals by decline activities of glutathione peroxidase dismutase or increase in the lifetime of free radicals with inhibited pretreatment of cells antioxidant like that alpha tocopherol. ELF and RF electromagnetic field maycan damaged DNA with raising level hydroxyl radicals in cells and it is can interact DNA and form mainly 8-hydroxy-2′–deoxyguanosine( 8-OHdG) adducts. Many study showed Electromagnetic field radiation(EMF) can change gene expression and conformation of protein. It may declineexpression of some genes such as superoxide dismutase orraise expressionof certain genes such as Hsps (heat shock proteins). ELF and RFelectromagnetic field can effects on homeostasis Ca2+ and alteration in important cellular and molecular processes such as differentiation, proliferation, gene expression, cytoskeletal reorganization and metabolism. Use of radio frequency electromagneticfield onsatellite jamming in Iran and some country may can harmful to human health and it could be a risk factor for cancer.